Time-course transcriptomics reveals that amino acids catabolism plays a key role in toxinogenesis and morphology in Clostridium tetani. (1st December 2020) - Orellana, Camila A; Zaragoza, Nicolas E; Licona-Cassani, Cuauhtemoc; Palfreyman, Robin W; Cowie, Nicholas; Moonen, Glenn; Moutafis, George; Power, John; Nielsen, Lars K; Marcellin, Esteban
Abstract: Tetanus is a fatal disease caused by Clostridium tetani infections. To prevent infections, a toxoid vaccine, developed almost a century ago, is routinely used in humans and animals. The vaccine is listed in the World Health Organisation list of Essential Medicines and can be produced and administered very cheaply in the developing world for less than one US Dollar per dose. Recent developments in both analytical tools and frameworks for systems biology provide industry with an opportunity to gain a deeper understanding of the parameters that determine C. tetani virulence and physiological behaviour in bioreactors. Here, we compared a traditional fermentation process with a fermentation medium supplemented with five heavily consumed amino acids. The experiment demonstrated that amino acid catabolism plays a key role in the virulence of C. tetani. The addition of the five amino acids favoured growth, decreased toxin production and changed C. tetani morphology. Using time-course transcriptomics, we created a "fermentation map", which shows that the tetanus toxin transcriptional regulator BotR, P21 and the tetanus toxin gene was downregulated. Moreover, this in-depth analysis revealed potential genes that might be involved in C. tetani virulence regulation. We observed differential expression of genes related to cell separation, surface/cell adhesion, pyrimidine biosynthesis and salvage, flagellar motility, and prophage genes. Overall, the fermentation map shows that, mediated by free amino acid concentrations, virulence in C. tetani is regulated at the transcriptional level and affects a plethora of metabolic functions.